المركز القانوني للأمين العام للبلدية - خليفي أحمد عابي – صابر بوحملة (جامعة محمد بوضياف المسيلة, 2018)
يتمحور موضوع بحثنا هذا حول المركز القانوني للأمين العام للبلدية، واشكالية تجسيده لمبدأ اللامركزية الادارية، من خلال الصلاحيات التي منحت له بموجب لمرسوم التنفيـــــذي 16-320 حيث تشكل البلدية في الجزائر الخلية الأولى والأساسية للجماعات المحلية، نظر اللدور الهام الذي تلعبه كموقع احتكاك مع المواطن، فهي تجسد صورة اللامركزية الادارية، وعليه تهدف دراستنا لتسليط الضوء عل منصب الامين العام للبلدية الذي كرس في ظل قانون البلدية 11-10 باعتبار ههيئة من هيئات البلدية، حيث حاول المشرع من خلاله تغطية الاختلالات الواقعة في التنظيم الهيكلي السابق ومنه قام المشرع باستحداث ادارة بلدية يتولى تنشيطها الامين العام. غيرأنه ورغم أهمية هذا المنصب فقد ظل سنوا تطويلة غائب عن النصوص القانونية التينظمته،لغاية صدورالمرسوم التنفيذي 16-320 الذي تضمن الأحكام الخاصة المطبقة عليه، من خلال النص على حقوقه وواجباته وكذا المهام المسنـــــــدة اليه، وكيفية تقييمه والشروط الواج توافرها لتعيينه This research focuses on the legal status of the Secretary-General of the Municipality and the problematic nature of the principle of administrative decentralization through the powers granted to him under Executive Decree 16-320. The municipality of Algeria is the first and basic cell of the local communities because of its important role as a site of contact with the citizen. It reflects the image of administrative decentralization. Our study aims at highlighting the position of the secretary general of the municipality, In which the legislator attempted to cover the imbalances in the previous structural structure, from which the legislator introduced a municipal administration to be revitalized by the secretary-general. However, despite the importance of this position, it remained for many years absent from the legal texts that it organized, until the issuance of Executive Decree 16-320, which included the special provisions applied to it, by stipulating his rights and duties as well as the tasks entrusted to him.
Keywords: الأمين العام . البلدية . اللامركزية . مصالح الجماعة الإقليمية